2013
DOI: 10.1007/s00403-013-1385-y
|View full text |Cite
|
Sign up to set email alerts
|

Fir honeydew honey flavonoids inhibit TNF-α-induced MMP-9 expression in human keratinocytes: a new action of honey in wound healing

Abstract: Matrix metalloproteinase-9 (MMP-9) appears to be a major protease responsible for the degradation of matrix and growth-promoting agents in chronic wounds. Honey has been successfully used for treating non-healing wounds associated with infections. However, the mechanisms of its action at the cellular level have remained poorly understood. The aim of this study was to investigate the effect of fir honeydew honey on TNF-α-induced MMP-9 expression and secretion from human keratinocytes (HaCaT) and to identify the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(58 citation statements)
references
References 36 publications
1
54
1
2
Order By: Relevance
“…Além disso, os flavonoides possuem capacidade de inibir a desgranulação de neutrófilos e reduzir a ativação do complemento, diminuindo assim a adesão de células inflamatórias ao endotélio e a resposta inflamatória (Nijveldt et al, 2001). Os flavonoides também inibem a produção de metaloproteinase-9 em queratinócitos humano durante o processo de cicatrização de feridas (Majtan et al, 2013). Taninos, também presentes no EE da S. obtusifolium, são capazes de inibir as enzimas COX-2 e/ou iNOS (Carvalho, 2004).…”
Section: Resultado E Discussãounclassified
“…Além disso, os flavonoides possuem capacidade de inibir a desgranulação de neutrófilos e reduzir a ativação do complemento, diminuindo assim a adesão de células inflamatórias ao endotélio e a resposta inflamatória (Nijveldt et al, 2001). Os flavonoides também inibem a produção de metaloproteinase-9 em queratinócitos humano durante o processo de cicatrização de feridas (Majtan et al, 2013). Taninos, também presentes no EE da S. obtusifolium, são capazes de inibir as enzimas COX-2 e/ou iNOS (Carvalho, 2004).…”
Section: Resultado E Discussãounclassified
“…Contrary to the immunostimulatory effects of honey described above Majtan et al (2013) reported an anti-inflammatory effect of an aqueous extract of fir honeydew honey obtained from an apiary in Bardejov, Slovakia. In this study, the extract inhibited TNFα induced matrix metalloproteinase-9 (MMP-9) protein and mRNA production by human keratinocytes (HaCaT) cells as measured by ELISA and RT-PCR respectively.…”
Section: Immunomodulatory Properties Of Honey (Skin Cells): In Vitro mentioning
confidence: 61%
“…More recently, in vitro research has suggested that honeys of diverse floral origins can modulate the skin immune system; both immunostimulatory and antiinflammatory effects have been observed (Majtan, Kumar, Majtan, Walls & Klaudiny, 2009;Majtan et al, 2013). In this review, the scientific evidence for the immunomodulatory properties of honey in relation to disorders of the skin is evaluated and the mechanisms of the immunomodulatory properties explored.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is naturalized and cultivated in the tropics of America, Egypt, India and parts of the Middle East (Muhammad and Muhammad, 2005). The different parts of henna have been reported to exert antioxidant, hypoglycemic, antidiabetic, hepatoprotective, antibacterial, antifungal, anticancer and wound healing properties (Majtan et al, 2013;Hadagali and Chua, 2014;Rajashri and Sachin, 2014;El Bergadi et al, 2015;Devasvaran and Yong, 2016;Mohamed et al, 2016).…”
Section: Introductionmentioning
confidence: 99%